Stigma Epilepsi Dari Masyarakat dan ODE - Natasya, Natasya (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Epilepsy is a chronic disorder of the brain characterized by recurrent seizures. In Indonesia, epilepsy is still often seen as a curse or possessed by an evil spirit, which in turn creates a negative stigma against epilepsy. This study aims to look at the stigma of epilepsy from the public and people with epilepsy (PWE). Using a descriptive method through questionnaires distributed to the Tarumanagara University area and to the PWE community for the period December 2022 - February 2023. With PWE criteria, students and employees at Tarumanagara University who willing to fill out the questionnaire. A total of 108 respondents from ordinary people and 57 PWE respondents participated in filling out the questionnaire. In terms of friendship: the general public wants to be friends with people with epilepsy (80.4%), while PWE are afraid of being shunned by friends and the surrounding environment (41.4%). In terms of education: the general public considers epilepsy can affect a sufferer's education (24.3%), while PWE find it difficult to reach their goals where epilepsy can interfere with a person's cognitive impairment (27.0%). In the field of work: ordinary people are willing to employ a person with epilepsy (56.1%), while PWE think that it is difficult for people with epilepsy to find work (45.0%). Based on this description, the stigma of epilepsy in society does not hinder PWE from socializing and working, but the stigma within PWE hinders PWE themselves from socializing and working. But with regard to education, there are not too many differences regarding education in PWE and how PWE achieves their goals. This is what seems to encourage many people with epilepsy who prefer to work as entrepreneurs rather than work as employees because they find it difficult to find work.